394 PROGNOSTIC POWER OF A NEW INDEX OF RIGHT VENTRICLE-PULMONARY ARTERY COUPLING BASED ON RIGHT VENTRICULAR VOLUMES IN PATIENTS WITH SECONDARY TRICUSPID REGURGITATION. (15th December 2022) - Cascella, Andrea; Gavazzoni, Mara; Muraru, Denisa; Heilbron, Francesca; Caravita, Sergio; Tomaselli, Michele; Parati, Gianfranco; Badano, Luigi Paolo
Abstract: Background: Echocardiographic surrogates of right ventricle (RV) to pulmonary artery (PA) coupling have been reported to be associated with outcomes in secondary tricuspid regurgitation (STR). However, pulmonary artery systolic pressure (PASP) is difficult to be estimated using echocardiography in patients with severe STR and 3D-derived indexes are loading dependent. Objectives: To evaluate the predictive power of a new surrogate of RV-PA coupling obtained using RV volumes measured by three-dimensional echocardiography (3DE), accounting for regurgitant volume of STR. Methods: Patients with moderate or severe STR were enrolled. The primary outcome was the composite endpoint of death from any cause and heart failure hospitalization. Results: 180 patients were included with a median follow up of 24 months (IQR: 2-48); 72 patients (40%) reached the primary endpoint. Among the tested RV-PA coupling indexes, the ratio between (RV stroke volume [SV]-regurgitant volume)/ RV End-systolic volume (ESV) (i.e. RV forward SV/ESV) showed the highest predictive power of the combined endpoint (AUC 0.85 [IC 95% 0.78-0.93]), with a threshold value of 0.40. It was followed by RV ejection fraction/PASP (AUC 0.75 [IC 95% 0.67-0.84]), and TAPSE/PASP (AUC 0.76 [IC 95% 0.68-0.85]). Severe TR (HR 2.04 [CI 95%: 1.10-3.78], p=0.02), TAPSE/PASP <0.36 mm/mmHg (HR 2.39 [CI 95%: 1.26-4.54], p=0.01), and RV forward SV/ESV <0.40 (HR 5.45 [CI 95% 2.47-12.00], p<0.001) were independently associated with the combined endpoint. Conclusions: RV forward SV/ESV is able to stratify the risk of death and HF hospitalization in patients with STR when added to TR severity, RV ejection fraction and TAPSE/PASP